USE OF CRYPTOCURRENCIES BITCOIN AND ETHEREUM IN THE FIELD OF E-COMMERCE: CASE STUDY OF UKRAINE - V. Suslenko; T. Zatonatska; O. Dluhopolskyi; A. Kuznyetsova (Фінансово-кредитна діяльність: проблеми теорії та практики, 2022)
Abstract. The article examines integration of cryptocurrencies as electronic payment systems in e-commerce enterprises. Practical usage of Ethereum and Bitcoin cryptocurrencies as electronic payment systems, as well as factors that may affect their functionality are studied. Coinbase Commerce and Bitpay, as market leaders in cryptocurrency payment providers, were analyzed to compare integration issues and commission analysis with traditional payment systems LiqPay, PayPal. It is determined that the factors influencing the integration of cryptocurrencies in the enterprise include the field in which this enterprise is operating, instability of the national currency, development of information technology. It has been proven that e-commerce companies specializing on selling consumer goods could use hybrid cryptocurrency payments in Bitcoin in 50% of transactions and Ethereum in 65% of transactions in the studied timeframe to reduce the cost of the transaction compared to the LiqPay system.